EXPERIMENTAL ATHEROSCLEROSIS AND PREDICTORS OF RENEWAL OF FUNCTION OF LIVER AT INTRODUCTION OF CRYOPRESERVATION OF PLACENTA - Kondakov, I.; Zhulikova, E.; Yurchenko, T.; Sharlay, T. (World of Medicine and Biology, 2012)
Introduction of allogenic cryopreservation placenta on a background spontaneous regress of experimental atherosclerosis, resulted in the acceleration of regeneration processes in the liver of experimental animals. There was an improvement of hemodynamics, the amount of binuclear hepatocytes diminished for certain, findings complement the before got results about the state of lipid metabolism.